Perceptions and Motivations of Japanese Medical Students Regarding Course Evaluations: A Cultural Perspective - Suzuki S; Imafuku R; Kawakami C; Abe Y; Jego EH; Hidai C; Saiki T (Advances in Medical Education and Practice)
Saki Suzuki,1– 3 Rintaro Imafuku,3 Chihiro Kawakami,3 Yuriko Abe,1,2 Eric H Jego,2 Chiaki Hidai,1,2 Takuya Saiki3 1Division of Medical Education, Nihon University School of Medicine, Itabashi-ku, Tokyo, Japan; 2Medical Education Center, Nihon University School of Medicine, Itabashi-ku, Tokyo, Japan; 3Medical Education Development Center, Gifu University, Yanagido, Gifu, JapanCorrespondence: Saki Suzuki, Division of Medical Education, Nihon University School of Medicine, 30-1 Oyaguchi Kamicho, Itabashi-ku, Tokyo, 173-8610, Japan, Tel +81 3 3972 8111, Email suzuki.saki@nihon-u.ac.jpPurpose: Course evaluations are critical for improving educational practices; however, their results can be influenced by various unexpected factors, including cultural values. Despite several studies on cultural dimensions in course evaluations, Japanese students were rarely the focus of evaluation in the Asian context. Data on Japanese students’ evaluation practices may reveal diverse behavioral patterns in Asian countries, highlighting the value of country-specific studies to uncover unique educational contexts. This study explores, through a cultural lens, how Japanese medical students perceive course evaluations and the factors influencing their participation.Methods: Four Focus Groups were created with 23 third- and fourth-year medical students. The recorded discussion data were analyzed using a thematic analysis approach by applying Hofstede’s model of six cultural dimensions as a theoretical framework.Results: This study identified three main themes influencing student participation in course evaluations: their emotions, insufficient understanding of the evaluations’ significance, and logistics impacting student motivation. Gratitude positively influenced their decision to participate in course evaluations, whereas anger, anxiety about presumptuousness, fear and indifference had a negative impact. Additionally, their willingness to participate was positively influenced by the perceived benefits for future students. Logistics, including the timing of evaluations and the design of the online evaluation form, also contributed to either encouraging or discouraging their participation.Conclusion: This study has illuminated factors shaping medical students’ perceptions and motivations regarding course evaluation through Hofstede’s model. These include “perfectionism” associated with decisiveness, “the attitude of accepting the status” linked to restraint, “teacher-centered education” and “respect for authority” related to power distance, “peer pressure” reflecting collectivism, and “risk avoidance” tied to uncertainty avoidance. Understanding these cultural nuances is crucial for the effective implementation of course evaluations in medical schools, as they offer valuable insights into how cultural contexts influence perceptions and motivations across diverse educational environments.Keywords: course evaluation, medical student, Hofstede, cultural dimensions, Confucian, student attitudes